Recent advances in the TDR-based leak detection system for pipeline inspection - Cataldo, Andrea; De Benedetto, Egidio; Cannazza, Giuseppe; Masciullo, Antonio; Giaquinto, Nicola; D’Aucelli, Giuseppe Maria; Costantino, Nicola; De Leo, Antonio; Miraglia, Marcello (Measurement : journal of the International Measurement Confederation, 2017)
•New design of sensing element and the use of a new connection modality.•Description of the technical aspects for the implementation of the system.•Comparative measurements using two TDR instruments to localize leaks. In this paper, the most recent advances in the time-domain reflectometry (TDR)-based system for leak-localization in underground pipes are described in detail. More specifically, a new design of sensing element and the use of a new connection modality are proposed. Thanks to these new features, the practical implementation of the system becomes much quicker and its use more effective. Additionally, the present work also describes all the practical aspects and technical details (from installation to functional tests), related to the practical implementation of the system. Finally, to assess the possibility of further increasing the cost-effectiveness of the TDR-based leak localization system, experimental tests were carried out by comparatively using two TDR instruments, differing in specifications and costs, to identify the position of a leak.